2019
DOI: 10.11118/actaun201967051171
|View full text |Cite
|
Sign up to set email alerts
|

Endophytic Bacterial Consortium Originated from Forestry Plant Roots and Their Nematicidal Activity against Meloidogyne incognita Infestation in Greenhouse

Abstract: Yield loss due to root-knot nematode Meloidogyne incognita infection is reported to reach 35%, depends on factors contributing to infection. Application of several endophytic bacterial isolates (bacterial consortium) to control pathogenic infection is reported to be more effective compared to the application of single bacterial isolate. This study was aimed to obtain endophytic bacterial consortium originated from forestry plant that is effective to control root-knot nematode. The study was conducted through b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(30 citation statements)
references
References 33 publications
2
25
0
3
Order By: Relevance
“…Data were analyzed using Analysis of Variance (ANOVA), if there was a difference, the analysis was continued using a continuous test following the Duncan Multiple Range Test (DMRT) method with 95% degree of confidence. The analysis was performed using the DSAASTAT version 1.101 program (Munif et al 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Data were analyzed using Analysis of Variance (ANOVA), if there was a difference, the analysis was continued using a continuous test following the Duncan Multiple Range Test (DMRT) method with 95% degree of confidence. The analysis was performed using the DSAASTAT version 1.101 program (Munif et al 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Many reports have shown that PGPB can promote plant growth and enhance yield from plants affected by nematodes under greenhouse, microplot and field conditions [ 6 , 22 , 43 , 55 , 56 , 57 , 58 , 59 , 60 ]. A microplot experiment was carried out in the National Agriculture Research Center (Tsukuba, Japan) on low-humic and M.incognita infested soil to ivestigate the nematicidal effects of Pasteuria penetrans .…”
Section: Growth Stimulation and Productivity Of Plantsmentioning
confidence: 99%
“…Metabolites of both bacteria reduced the number of egg masses and root galls, while P. protegens also promoted seed germination and plant growth. In another study, Munif et al [ 78 ] obtained 81% mortality of J2s and 81% reduction in egg-hatch of M. incognita with a consortium of bacterial endophytes isolated from trees. Details of these endophytic species were not revealed, however.…”
Section: Endophytes As Bionematicidesmentioning
confidence: 99%
“…Some consider that a consortium of beneficial microorganisms is better than using a single microorganism and several commercial products based on microbial consortia have been developed in the recent years [ 78 , 91 ]. However, consortia may not always provide better control than a single endophyte due to potential negative interactions among the members.…”
Section: Endophytes As Bionematicidesmentioning
confidence: 99%